Design and Development of a Smart Automated Packaging System for Poultry Drumsticks - Sidhant Sanjay Kulkarni; Sakshi Mahendra Abhale; Asmita Amol Aher; Shubham Kiran Sonawane; Prasad Kailas Aher; R. A. Kapgate (International Journal of Machine Systems and Manufacturing Technology, 2026)
The present work aims to design and implement an automated packaging system for poultry drumsticks that enhances operational efficiency, product quality, and adaptability. The integrated system offers a solution that complies with industrial quality and safety standards by sorting products, getting accurate weighing, and efficiently portioning food into 1-kilogram standardized units. By effectively reducing human involvement, operational inefficiencies, workforce requirements, and contamination hazards, the automation system becomes sufficiently adaptable to meet various production demands. As its primary creativity, the system replaces conventional wrapping techniques with a knotting wrapping method. Reduced use of materials, enhanced sanitation, faster processing, and less maintenance are just a few benefits of this strategy.Scalability is prioritized in the automation solution's design, which also offers flexible packaging choices that optimize operations and set the foundation for the future. These affordable food packaging solutions ensure hygienic practices and technological sophistication. In addition to these core functionalities, the proposed system integrates sensor-based monitoring and programmable control mechanisms to ensure consistent performance and precision throughout the packaging cycle. Advanced load cells and conveyor synchronization enable real-time weight verification and automatic rejection of non-conforming units, thereby minimizing product giveaway and ensuring uniformity. The system architecture is designed with modular components, allowing easy upgrades, maintenance, and customization according to varying production capacities and packaging requirements. The automation framework also incorporates safety interlocks and food-grade materials to comply with stringent food safety regulations and industry standards. By streamlining the workflow from sorting to final sealing, the system significantly reduces processing time while maintaining product integrity and freshness. Furthermore, data acquisition and monitoring features provide production analytics that support quality control, traceability, and decision-making processes. Economic analysis indicates that the reduction in labor dependency, material wastage, and operational downtime contributes to long-term cost savings and improved return on investment. The proposed solution not only enhances productivity but also supports sustainable practices by optimizing packaging material usage and reducing environmental impact. Overall, the developed automated poultry drumstick packaging system demonstrates a reliable, scalable, and innovative approach to modern food processing challenges, aligning with evolving industry demands and consumer expectations.
Keywords: Automation; Knotting Mechanism; Precise Weighing; hygiene